Child Welfare, Indigenous Children and Children’s Rights in Canada / Bem-Estar da Criança, Crianças Indígenas e Direitos da Criança no Canadá - Stevenson, Allyson (Revista Direito e Práxis, 2019)
DOI: 10.1590/2179-8966/2019/40639 Abstract: In Canada, Indigenous children have been removed from their families and communities for residential schooling and for adoption and fostering by the state. These historic and ongoing policies have contributed to a general lack of awareness and respect for the rights of Indigenous children as children, as well as Indigenous rights bearers. This paper examines the ways in which historic Indigenous transracial adoption projects acted as a means of public education for ignorance, and argues there is an urgent need for increased public and academic attention to Indigenous children’s rights as both universal children’s rights and Indigenous rights. Keywords: Indigenous Rights, Adoption, Children. Resumo: No Canadá, crianças indígenas foram removidas de suas famílias e comunidades para educação residencial e para adoção e acolhimento institucional pelo estado. Essas políticas históricas e em andamento contribuíram para uma falta geral de conscientização e respeito pelos direitos das crianças indígenas desde uma perspectiva de suas condições como crianças, bem como de portadoras de direitos indígenas. Este artigo examina as maneiras pelas quais projetos históricos de adoção indígena trans-racista agiram como um meio de educação pública para a ignorância, e argumenta que há uma necessidade urgente de maior atenção pública e acadêmica aos direitos das crianças indígenas como direitos das crianças e direitos indígenas, ambos de caráter universal. Palavras-chave: Direitos Indígenas, Adoção, Crianças.